Traversing organizational scales in plant salt-stress responses. (February 2015) - Dinneny, José R
Highlights: Roots exhibit halotropism to avoid saline soil. Spatiotemporal transcriptional map reveals dynamic regulation of growth by hormones. Rapid Ca 2+ waves mediate systemic acclimation to salt. Ethylene promotes ROS accumulation to inhibit transport of sodium to shoot. ABA protein–protein interaction networks uncover novel players in stress signaling. Abstract : Modern society has developed in large part due to our ability to reliably grow plants for food and renewable resources. Predicted increases in environmental variability will impact agricultural productivity and may have extensive secondary effects on the stability of our society. Thus, a concerted effort to understand plant response strategies to stress is needed. High salinity is an agriculturally important environmental stress and generates complex effects on the physiology of the plant. The abiotic-stress-associated hormone, abscisic acid (ABA), mediates a major component of this response. I highlight recent work studying salt-stress responses at different spatial and organizational scales from the action of ABA in specific cell types to global networks of proteins that predict critical regulatory events during acclimation.